Legal Challenges in the Enforcement of Foreign Arbitral Awards in Nigeria - Kudirat, Magaji (University of Ilorin, 2021)
Businessmen have a choice in the resolution of disputes, they may elect litigation or submit to arbitration. Delays, outrageous cost and undue technicalities associated with courts, makes commercial arbitration the preferred mode of settlement in the business world. However, the recalcitrance of an award-debtor to comply with the terms of the award necessitates the intervention of the courts. Nigeria has provisions for enforcement of foreign arbitral awards within her legal system. However, reliance on courts for enforcing foreign awards frequently frustrates the gains initially made by arbitration. Enforcement of arbitral awards via the courts has numerous legal challenges. This study is therefore aimed at analysing the challenges facing enforcement of foreign awards in Nigeria. The objectives of the study were to: (i) analyse the impact of extant legal regimes on the recognition and enforcement of foreign awards in Nigeria; (ii) examine the effects of the concepts of arbitrability and public policy exceptions on the enforcement of awards in Nigeria; (iii) examine the challenges inherent in judicial review on the enforcement of foreign awards in Nigeria; and (iv) examine the adequacy of the Arbitration and Conciliation Act 1988 (ACA 1988) in the recognition and enforcement of Islamic commercial arbitral awards. The study employed doctrinal methodology of legal research where primary and secondary of legal materials were subjected to descriptive and content analysis. The primary sources used were legislations, regulations, treaties, conventions and case laws, while secondary sources used were texts books, journals, internet materials, conferences and seminars papers. The findings of the study were that: i. the provisions of the laws regulating enforcement of foreign arbitral awards in Nigeria, particularly, Sections 51 and 54 of ACA 1988 have inherent and procedural defects, thus preventing the smooth enforcement of the award; ii. the narrow interpretation by the Nigerian courts on ‘arbitrability’ based on Sections 54 and 57 of ACA 1988 which restricts disputes to contractual and commercial disputes only, prevents the enforcement of foreign awards from jurisdictions with liberal interpretation. iii. the amorphous nature of the scope of public policy creates a challenge for the courts in Nigeria in determining whether a foreign award violates the country’s public policy or not; iv. the powers of the courts to set aside foreign awards based on grounds contained in Sections 29, 30 and 48 ACA 1988 are open-ended and allow the courts to examine the merit of the disputes rather than limit themselves to the validity of the award for enforcement; v. the provisions of ACA 1988 on enforcement of foreign arbitral awards do not consider the idiosyncrasies of awards from Islamic law jurisdictions, despite growing investors’ interests in Islamic commercial transactions. The study concluded that it is obvious that the various legal challenges identified showed that the existing legal frameworks on enforcement of foreign arbitral award in Nigeria are weak and ineffective. The study therefore recommended that the Nigerian arbitral laws in particular, the provisions on enforcement of arbitral awards under ACA 1988 should be amended.
Keywords: Enforcement; Foreign Arbitral Awards; Legal Challenges; Nigeria

The legal nature of debt securities in South African law - Beer, Johan Philip de (Stellenbosch University, 2021)
The problem statement of this thesis is ascertaining the legal nature of debt securities in furtherance of a consistent and coherent legal description of the South African positive law as it relates to this class of instruments. It focuses on four core issues: the legal history, legal nature, classification, and current legal issues relating to debt securities. Historical and analytic-systemic approaches to the problem statement make up Part 1 of the study. The historical approach shows an emergent commoditisation of debt, which is an important phenomenon in the analysis of securities law. It further shows a great deal of English influence in the development of the South African legal environment, most notably in terms of company law (as the primary driver of securities law) and the financial marketplace, its institutions and its regulation. Also highlighted is a notable scarcity of debt securities relative to equities, which materially impacted legislative developments. Finally, it points to an increase in the legal importance of the “securities” concept as a legal term to describe and govern debt and equity securities. Thereafter the analytic-systemic approach is used to identify a set of private law-rooted first principles applicable to South African registered securities, and herefore to debt securities as well. It posits that these securities should be understood conceptually as comprised two interdependent but functionally separate legal objects, rather than in terms of two different kinds of ownership (i.e. beneficial and registered). The first object is the "security instrument”, a locus for (holdership of) the incidents that flow from the entitlement of determination (beskikkingsbevoegdheid) over the underlying complex of rights and competencies of registered securities. These can be understood as incidents of execution. The second is the "security asset”, a locus for (holdership of) the incidents that flow from the entitlement of enjoyment (genotsbevoegdheid) over that underlying complex, and corresponds with the proprietary, patrimonial dimension of securities. These can be understood as incidents of enjoyment. This construction enables a more coherent understanding of the sui generis relationship of agency between beneficial owner and her nominee, as well as of the dynamics of ownership and quasi-possessio. These insights are then applied to the uncertificated environment, addressing a number of difficult and uncertain problems within the system that enables uncertificated securities and their holdership. Finally the particularly difficult issue of how to classify (and therefore identify) debt securities is dealt with. Here it is concluded that a typological approach is the only viable methodology to deal with this problem, and a number of necessary and thereafter possible classificatory indicia are outlined for this purpose. The functional-policy approach makes up Part 2 of the study. It is a policy-aware application of the theoretical framework developed to a select number of themes and legal issues of the current environment. Principally it shows that the reconceptualisation of registered securities has explanatory and problem-solving value, specifically relating to transfer, the granting of limited real interests, good faith acquisition, and the protection of holdership of certificated and uncertificated securities.
Keywords: Beneficial ownership; Debt and equity Securities; Securities; Securities industry; South Africa; Titre de créance